The development of student worksheet assisted by interactive multimedia of photoelectric effect to build science process skills - Payudi Payudi; Chandra Ertikanto; Noor Fadiawati; Agus Suyatna (International Journal of Science and Applied Science: Conference Series, 2017)
This research aims to produce student worksheet based on interactive multimedia on photoelectric effect to grow science process skills that are attractive, easy, useful, and study to improve students learning out comes. The development design used in this research by Sugiono which implemented in 8 stages, they are potential and problem, data collecting, product design, validation design, revision design, product trial, product, and trial usage. Trial usage of the product was conducted at SMA Negeri 2 Bandar Lampung in October 2016 to November 2016 and the research subject was twelve grade classes. The sampling technique of product trial subjects done by purpose sampling, it took two same classes. One class used as an experimental class and the other class as a control class. Trial product design used Matching-Only Pretest-Post test Control Group Design method. Data collecting technique used questionnaire and test (pretest and post test). The data were analyzed by using a descriptive quantitative method. The conclusions of the research are: (1) Student worksheet to build scientific process skills on photoelectric effect should include predicting and hypothesizing activities, planning the experiment, doing the practicum, interpreting the observation, and communicating. (2) Student worksheet of development result has an attractiveness level with the average score is 3.27 or 81.74% with “interesting” category, ease level with the average score is 3.25 or 81.32 with “simple”, and usefulness level with the average score is 3.21 or 80.13% of “useful” category. (3) Student worksheet of development result is effective to improve students learning outcomes in science process skills with N-gain average is 0.63 with the medium.